Health-related Quality of Life across the Anxiety Disorders: Findings from a Sample of Primary Care Patients - Beard, Courtney (2010)
Previous studies have not compared Health-related Quality of Life (HR-QoL) across all DSM-IV anxiety disorders and comorbid conditions. We compared the effects of each anxiety disorder on HR-QoL, controlling for demographic variables, medical conditions, and comorbid Axis I disorders. Data are obtained from the Primary Care Anxiety Project (PCAP), a naturalistic, longitudinal study of anxiety disorders in 539 primary care patients. Each of the anxiety disorders was associated with worse self-reported physical and mental functioning compared to general population means. While all of the anxiety disorders were univariate predictors of specific domains of HR-QoL, only presence of Posttraumatic Stress and Disorder (PTSD) and comorbid Depressive Disorder (MDD) uniquely predicted worse functioning on both self-report and interview measures. The current study extends previous research by showing that different anxiety disorders and comorbid conditions may be associated with impairment in specific domains of HR-QoL.